Power, madness and anarchy: a genealogy of agonism in Michel Foucault - Rodrigues, Thiago (História: Questões e Debates, 2019)
This article takes the Michel Foucault’s 1974 course at Collège de France called Psychiatric Power as a first genealogical exercise by the philosopher to perform his “agonistic turn” that would result in his reflections on power, politics and ethics. The originality of this article lays at the connection seen between Foucault’s Nietzschean approach and the anarchist pioneer Pierre-Joseph Proudhon at his almost unknown work La Guerre et la Paix (War and Peace), published in 1861. I try to explore these connections as a way to think contemporary politics beyond the traditional canon that still places the state (or its new arrangements) as the only source of power.